2015
DOI: 10.1016/j.jphs.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of afimoxifene, endoxifen, raloxifene, and fulvestrant by the human cytosolic sulfotransferases (SULTs): A systematic analysis

Abstract: Previous studies demonstrated that sulfate conjugation is involved in the metabolism of three commonly used breast cancer drugs, tamoxifen, raloxifene and fulvestrant. The current study was designed to systematically identify the human cytosolic sulfotransferases (SULTs) that are capable of sulfating raloxifene, fulvestrant, and two active metabolites of tamoxifen, afimoxifene and endoxifen. A systematic analysis using 13 known human SULTs revealed SULT1A1 and SULT1C4 as the major SULTs responsible for the sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, no pharmacokinetic data are available and no further progress on pre-clinical studies have been reported since 2010. Indeed, these attempts focused on modifications made primarily to the long alkyl chain to increase polarity and solubility but failed to address the main problem that is responsible for the poor bioavailability of fulvestrant, that is, fulvestrant undergoes rapid and extensive O-glucuronidation [ 21 22 ] and O-sulfation [ 23 24 ] to form polar metabolites that are inactivated and undergo rapid systemic clearance.…”
Section: Introductionmentioning
confidence: 99%
“…However, no pharmacokinetic data are available and no further progress on pre-clinical studies have been reported since 2010. Indeed, these attempts focused on modifications made primarily to the long alkyl chain to increase polarity and solubility but failed to address the main problem that is responsible for the poor bioavailability of fulvestrant, that is, fulvestrant undergoes rapid and extensive O-glucuronidation [ 21 22 ] and O-sulfation [ 23 24 ] to form polar metabolites that are inactivated and undergo rapid systemic clearance.…”
Section: Introductionmentioning
confidence: 99%
“…SULT1A1 is generally recognized as the major xenobiotic-metabolizing SULT isoform that is responsible for the metabolism of reactive compounds (e.g., benzylic alcohols and aromatic hydroxylamines), which are associated with carcinogenesis 9 . Sulfate conjugation by other SULT enzymes (SULT1A3, SULT1E1 and SULT1B1) may result in the activation or inactivation of anti-cancer drugs (e.g., raloxifene, sesamol, fulvestrant, and resveratrol), thereby affecting their anti-tumor effects 1013 . In addition, Huang LR et al .…”
Section: Introductionmentioning
confidence: 99%
“…SULT1E1 and SULT2A1 mRNA levels were below the detection limit in both cell lines [20]. As SULT1C4 mRNA only has been found at high levels in human fetal lung, liver, small intestine, and kidney, and at low levels in adult kidney, ovary, and spinal cord but not in breast tissue [24], we hypothesized that SULT1A1 may mainly contribute to curcumin sulfation in ZR-75-1 and MDA-MB-231 cells leading to decreased anticancer activity. Our hypothesis is further supported by data of Irison and coworkers who indeed showed that curcumin sulfate has less biological activities compared to curcumin [11].…”
Section: Discussionmentioning
confidence: 98%